U.S. Copyright Renewals, 1960 January - June - Library of Congress. Copyright Office (Salt Lake City, UT : Project Gutenberg, 2004)
"U.S. Copyright Renewals, 1960 January - June" is a comprehensive reference work that chronicles copyright renewal registrations made between January and June of 1960. The book is likely a product of the mid-20th century, reflecting the evolving landscape of intellectual property during that time. Its central focus is on generating a detailed alphabetical list of various works, including books, pamphlets, and serials along with the relevant information for both original and renewed registrations, providing a vital resource for researchers and librarians interested in copyright history. The opening of this work introduces the organizational structure of the list that follows, noting the arrangement is primarily alphabetical by author or title. It also highlights the inclusion of detailed registration information$1 (Bsuch as dates, authors, and descriptions$1 (Bcreating a thorough header that sets the tone for the data provided in the subsequent pages. As this is just the beginning, it primarily outlines the process and intentions behind documenting these renewals without delving into the specific titles or authors that will be detailed later in the publication. The content aims to facilitate access to information about works that retained copyright protections during this significant period. (This is an automatically generated summary.)s
Release date is 2004-03-01
Produced by Michael Dyck, Charles Franks, Steve Schulze, pourlean, and the Online Distributed Proofreading team, using page images supplied by the Universal Library Project at Carnegie Mellon University
Keywords: Copyright -- United States -- Catalogs